Pratityasamutyapad Siddhant Se Anishwarwad Siddhant Ka Vikas – Ek Bodhya Darshnik Vishleshan - Abhinav Divyanshu (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2018)
In the presented philosophical research paper, light has been thrown on the philosophical aspects of Jain religion. In this research paper, the philosophical principles of Jainism have been discussed, along with how one philosophy or theory develops from another philosophy or theory, and what its results or consequences are. Along with this, it has also been discussed what influence philosophies have on religion and what influence religion has on society. It has also been examined what differences arise between the thoughts of one religion and another religion.